Angiotensin-converting enzyme gene does not contribute to genetic predisposition to elite soccer`s performance in Italians - Massidda, M.; Calò, C.; Corrias, L.; Vona, G.; Piras, F.; Folletti, S.; Scorcu, M. (Medicina dello Sport, 2011)
Aim. The purpose of this study was to verify the association between the ACE I/D polymorphism and elite athletes status in Italian soccer players.